The Existence of Islamic Student Organizations: How Student Organizations of Nahdlatul Ulama and Muhammadiyah Respond to the Challenges of the 21st Century - Nuruzzaman, Muhammad Adib; Ummah, Ilmi Izzatul; Faizah, Nur (AN NUR: Jurnal Studi Islam, 2025)
In the digital era, students face rapid changes in various fields, ranging from technological advancements to global culture, which often clash with Islamic values. This paper explains how the Nahdlatul Ulama Student Association (IPNU) and the Muhammadiyah Student Association (IPM)—the two largest Islamic student organizations in Indonesia—respond to the challenges of the 21st century. Using qualitative methods and a multiple case study design, the research collected data through interviews, document reviews, and literature studies. The data were then analyzed using a cross-case analysis method to compare the strategies employed by IPNU and IPM. The aim is to provide updated insights into the existence of Islamic student organizations in empowering youth amidst the dynamics of 21st-century modernization. The findings reveal that Nahdlatul Ulama, with its "Islam Nusantara" philosophy, and Muhammadiyah, with its "Progressive Islam" philosophy, offer distinct contributions to Indonesian Muslims by maintaining Islamic identity while addressing the threats of pop culture in the face of globalization and remaining responsive to technological advancements. The Nahdlatul Ulama and Muhammadiyah student organizations empower their members by developing programs and activities tailored to the challenges they face, such as regular Islamic studies, technology training, and cultural counter-movements. With their unique characteristics and established empowerment patterns, these organizations, whose members are spread throughout Indonesia, can serve as role models for other Islamic communities in facilitating students and youth to grow into future leaders.